Modified secure AODV protocol to prevent wormhole attack in MANET. (28th November 2018) - Sankara Narayanan, S.; Murugaboopathi, G.
Summary: An Adhoc network is a combination of mobile nodes that works without centralized infrastructure. Every mobile node acts as host and routers. Furthermore, it also forward packets to other mobile nodes in network which are not within the direct transmission range. Mobile Ad hoc networks are easily exposed to various network layer attacks that include black hole, wormhole, and DOS attack. Wormhole attack is one among the severe attacks in MANET. Wormhole attacker receives the packets at any particular location in the network and disturbs the flow of packet by tunneling them to another location. In this paper, advanced mechanism is presented against these wormhole attacks in a MANET. Existing methods use Quality of Service (QoS) for entire network to detect attacks. Our method makes use of the packet delivery ratio and round trip time for each node, and it also detects active and passive attacks. Thus, the complete identification of wormhole attack is possible using the proposed method.